The prophet has shown the way - Abd Razak, Dzulkifli (2009)
EXACTLY a fortnight ago, Malaysians were reminded of two significant events. First, was the anniversary of the momentous national election held on March 8, the previous year. Interviews and opinions expressed in many newspapers, including this column, have been generally ambivalent in nature. Many felt precious time had been squandered when a common platform could have been sought to help the nation in facing the difficult times ahead. Given the minibudget announcement lately, it adds urgency to the situation.